Is the Lung Recruitment and Titrated Positive End Expiratory Pressure a Better Strategy as Compare to Low PEEP on Mortality in Patients with Acute Respiratory Distress Syndrome (Medical Forum Monthly, 2024)
Objective: To establish whether lung recruitment maneuver with PEEP titration reduces 28-day mortality in patients with moderate to severe ARDS in comparison to low PEEP strategy.Study Design: A Randomized Control Trial.Place and Duration: This study was conducted at the Intensive Care Unit Nishtar Hospital, Ibn e Sina Hospital, City Hospital, Multan from February 2016 to January 2018.Materials and Methods: A total of 490 patients were divided in two equal groups on the base of technique use as Lung recruitment maneuver with PEEP titration RP Group and in patents low PEEP (LP Group) was used to treat ARDS. Primary outcome was all-causes mortality up till 28 days. Secondary outcome included length of ICU and hospital stay, ventilator-free days, pneumothorax or barotrauma within seven days. Chi square test and student T tests were used to analyze data. P value < 0.05 was considered significant.Results: Death ≤28 days was observed as (58%) and (51%) for lung recruitment maneuver with PEEP titration group and low-PEEP group respectively. The difference was statistically insignificant (p=0.058). Deaths in intensive care unit, in hospital and within 6 months was observed as (62%) and (51.8%), (59.6%) and (50.6%), (70.6%) and (58%) for lung recruitment maneuver with PEEP titration group and low-PEEP group respectivelyConclusion: There is no significant difference of 28-day survival and decrease hospital stay, ICU Stay, and on ventilator duration, so lung recruitment maneuver and PEEP titration is not a better and effective strategy as compare to low PEEP.